Pannexin 1 regulates adipose stromal cell differentiation and fat accumulation. Issue 1 (December 2018) - Lee, Vanessa; Barr, Kevin; Kelly, John; Johnston, Danielle; Brown, Cody; Robb, Kevin; Sayedyahossein, Samar; Huang, Kenneth; Gros, Robert; Flynn, Lauren; Penuela, Silvia
Abstract Pannexin 1 (Panx1) is a channel-forming glycoprotein important in paracrine signaling and cellular development. In this study, we discovered that mice globally lacking Panx1 (KO) have significantly greater total fat mass and reduced lean mass compared to wild type (WT) mice under a normal diet. Despite having higher fat content, Panx1 KO mice on a high fat diet exhibited no differences in weight gain and blood markers of obesity as compared to WT controls, except for an increase in glucose and insulin levels. However, metabolic cage data revealed that these Panx1 KO mice display significantly increased activity levels, higher ambulatory activity, and reduced sleep duration relative to their WT littermates on a high-fat diet. To uncover the cellular mechanism responsible for the increased fat content in the KO, we isolated primary cultures of adipose-derived stromal cells (ASCs) from WT and KO fat pads. In WT ASCs we observed that Panx1 protein levels increase upon induction into an adipogenic lineage. ASCs isolated from Panx1 KO mice proliferate less but demonstrate enhanced adipogenic differentiation with increased intracellular lipid accumulation, glycerol-3-phosphate dehydrogenase (GPDH) enzyme activity, and adipokine secretion, as compared to WT ASCs. This was consistent with the increased adipocyte size and decreased adipocyte numbers observed in subcutaneous fat of the Panx1 KO mice compared to WT. We concluded that Panx1 plays a key role in adipose stromal cells during the early stages of adipogenic proliferation and differentiation, regulating fat accumulationin vivo .